PENERAPAN TERAPI SUPORTIF DENGAN TEKNIK GUIDANCE UNTUK MENINGKATKAN PENGHAYATAN MAKNA HIDUP PADA PENDERITA GANGGUAN BIPOLAR DI PONDOK PESANTREN AL HAMID CIBUBUR - Pardian, Delvi (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
AbstractThe lowness of the total and full comprehension of meaning of life on the sufferer of the bipolar disorder is marked by feeling having no aim of life, feeling of meaningless, easy to get bored, full ofÂ desperation, lack of interest and initiative, lack of passion of work, being not care, decreasing responsibility, questioning his/her existence in this world. The aims of this research are to find outÂ the description of the lowness of the total and full comprehension of meaning of life on the sufferer of the bipolar disorder and to apply the supportive therapy through guidance technique to raise the totalÂ and full comprehension of meaning of life on the sufferer of the bipolar disorder. The researchÂ methods that are used in this research are single case design and A-B-A design. The author uses observation, interview, and psychology tests such as WBIS, Graphic, SSCT and the intervention of supportive therapy through guidance technique. The result of intervention shows that there is a change on the subject of the research like being able to own the more meaningful life, caring more, having more responsibility, realizing her existence in this world, easy to be happy, and full of hope. Moreover, the result of the analysis of development of the intervention is supported by the result of the scale of pre-test which shows the high category and after the post-test is conducted, the result shows the middle category. The prognosis on the subject is positive in which she succeeds to improve her total and full comprehension of meaning of life.Â Â Keywords: supportive, therapy guidance technique, bipolar disorderÂ AbstrakRendahnya penghayatan makna hidup pada penderita gangguan bipolar ditandai dengan merasa tak memiliki tujuan hidup, merasa hidup tidak berarti, mudah bosan, penuh keputusasaan, hilangnya minat danÂ inisiatif,Â gairahÂ kerja menghilang,Â sikapnya acuhÂ takÂ acuh, Â menipisnya rasa tanggung jawab, Mempertanyakan kehadirannya di dunia. Tujuan dari penelitian ini adalah untuk mengetahui gambaran rendahnya penghayatan makna hidup pada penderita gangguan bipolar dan penerapan terapi suportif dengan Â teknik Â guidance Â untuk Â meningkatkan Â penghayatan Â maknaÂ hidup Â pada Â penderita Â gangguan bipolar. Â Metode Â penelitian Â yang Â digunakan Â dalam Â penelitian Â ini Â adalah Â single Â case Â design Â dan penelitian ini juga menggunakan â€œA-B-A designâ€. CP menggunakan observasi, wawancara, dan tes psikologi diantaranya WBIS, Grafis, SSCT dan intervensi terapi suportif dengan teknik guidance. Hasil intervensi menunjukan adanya perubahan dirinya mampu memiliki makna hidup lebih berarti, bersikap lebih peduli, tumbuhnya rasa tanggung jawab, mengetahui kehadiran di dunia, mudah senang dan penuh harapan kemudian hasil analisa perkembangan intervensi didukung dengan hasil skala pre-test menunjukkan Â padaÂ kategoriÂ tinggi. Â Setelah Â dilakukan Â post-test, Â hasilÂ menunjukkan Â pada Â kategori sedang. Prognosis pada subyek positif, dimana ia berhasil meningkatkan penghayatan makna hidupnya.Â Kata Kunci : terapi, suportif teknik guidance, gangguan bipolar